Fast and selective synthesis of mono-substituted sucrose methacrylate ester monomer - Rojas Sterling, Juan Camilo; Ortega, Julieth Orduña [UNESP]; Metzker, Gustavo [UNESP]; Boscolo, Mauricio [UNESP]; Mora Vargas, Jorge Andres [UNESP] (Elsevier, 2022)
Sucrose methacrylate (SM) is a key monomer for synthesizing biocompatible polymers with a carbohydrate core. However, controlled SM synthesis is challenging due to the possible formation of regio-isomers. This study describes SM synthesis that involves ultrasound irradiation of a homogeneous basic medium. The selectivity for mono-substituted SM was 86% within 30 min of reaction. The newly developed methodology is faster and more selective than that of mono-substituted SM synthesis already described in the literature.
Keywords: Methacrylate; Monomer; Sucrose ester; Ultrasound